Sanitation Environment and Helminth infection in Gowa District, Indonesia - Syamsul, Muharti; Kartini, Kartini; Aswadi, Aswadi; Syamsul, Muhammad Azrul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Healminth infection is one of the environmentally-based diseases which is a problem for public health. This research was conducted to know the description of latrines, trash bins, and clean water victims for people with healminth infection in the working area of the Kanjilo Health Center. This research uses quantitative research methods with a descriptive survey approach. The research sample was 32 samples. The data used are preliminary data from the medical records of the Kanjilo Health Center, Gowa Regency, while the data source used is secondary data. Data analysis using data processing research with SPSS. With a frequency distribution approach. The results showed that the worms that occurred were in a bad category, including 8 respondents who vomited worms and 24 who suffered from healminth infection. The results of this study found that both the availability of latrines, the availability of clean water and landfills, were all in the bad category, causing worms and vomiting in the community in the working area of the Kanjilo Health Center.